Algunos efectos de la expansión monetaria en las tasas de interés del mercado de préstamos - Rivas Santos, Pablo (2012)
This article states that an employer who provides a price increase in the market looking for loans willing to pay higher interest. The lender that provides a price increase, only provides loans if the market interest rises above the prevailing market interest in a situation where an expected retail price increases. The entrepreneur is not afraid that higher market interest, if you think your project will cost so that you can withstand that higher market interest. Such price increases planned unleashes an upward trend in market interest. By varying the ratio of monetary currency as occurred between 1963-1993 foreseeing a rise in prices, the upward trend prevailing market interest. So every loan is incorporated in a Compensation for rising prices. In the analysis of monetary expansion process, we assume that the presence of extra money in the loan market disturbs the adequacy of the economic system to the circumstances of the loan market, disturbing trend towards certain prices and interest rates. The variation of the ratio of monetary currency at the same time does not affect, nor in the same proportion, prices, wages and interest. Such variation affects the interest because that different reaction rates, changes in income and wealth people. The temporary modification of interest is further evidence that different reaction rates. The earlier you go to market the new money loan, more interest will be affected violence.